IMPLEMENTASI PEMBELAJARAN BAHASA INGGRIS DENGAN MEDIA ANIMASI BERBASIS CERITA RAKYAT UNTUK MENINGKATKAN KOMPETENSI MENULIS NARASI (Studi Pada Siswa kelas VIII A MTS Al Huda Gondangrejo Karanganyar Tahun Akademik 2013/2014 ) - Riyani, Ayu Istiana Sari (UNIVERSITAS SLAMET RIYADI, 2015)
The aims of this research is to describe the implementation of animation media based onfolklore at the seventh grade student of MTS Al Huda Gondangrejo Karanganyar 2013/2014academic year.The method used in this research is classroom action research which consists of fourstages: planning, acting, observing, and reflecting. The research was conducted in two cycles.This subject of the research was class VIII A MTS Al Huda Gondangrejo. The data obtained werefrom quantitative and qualitative data. The quantitative data were collected from pre test andpost test students writing mean scores. The qualitative data were collected by using sometechniques including test and non test.The research findings prove that the use of animation media based on folklore can improvethe students writing skill. The improvement of students writing skill included 1) content, 2)organization, 3) vocabulary, 4) grammar, and 5) mechanic. The improvements are clearly seenon their mean score in every cycle. The mean of score of the pre-test was 65, 19, the mean ofscore of post test one was 68,3 the mean of score of post test two was 71,06. From the descriptionabove, it shows that there is an improvement of students writing skill. It means that animationmedia based on folklore can improve the students writing skill on narrative.Key words: Media, Animation, Folklore, Writing Skill, Narrative.